Adapting critical infrastructure to climate change: A scoping review. Issue 135 (September 2022) - Huddleston, Pippa; Smith, Tim; White, Iain; Elrick-Barr, Carmen
Abstract: Critical infrastructure is a foundational component of a functional society and is under threat from the impacts of climate change. To ensure communities are not left without fundamental supplies and services, the adaptation of critical infrastructure to climate change needs to be understood holistically. This paper uses a scoping literature review to investigate the relationship between critical infrastructure and climate change. In the absence of a common definition for adaptive critical infrastructure, an outcomes-based definition is proposed that captures the four types of critical infrastructure: physical, ecological, institutional and cultural. A typology was developed to critically interrogate the focus of adaptive critical infrastructure. It shows that the focus across elements such as conceptualisation and management ranges from tangible to intangible infrastructure, and from positivist to interpretivist in approach. The literature review identified relationship-building as a key management objective across the spectrums. The typology contributes knowledge on how the choice of infrastructure focus and adaptation methods influences adaptation outcomes and path dependencies. Highlights: There are four different types of critical infrastructure: physical, ecological, institutional and cultural. Current definitions of critical infrastructure prioritise physical assets. Critical infrastructure needs to pay more regard to climate change impacts. A definition for adaptive critical infrastructure is proposed that includes tangible and intangible systems.